Potential for Cattle Business Development in the Buffer Zone of Mount Leuser National Park, Bahorok District, Indonesia - Apriansyah Irgiadi,R; Edhy Mirwandhono; Ahmad Sadeli (Jurnal Peternakan Integratif, 2024)
Local communities in Bahorok District are highly dependent on the agricultural and livestock sectors as their main livelihoods. The environment and abundant natural resources cause a profitable for the community to raise livestock.This study aims to to examine potential development of cattle farming (financial and economic aspects) in the buffer zone of Gunung Leuser National Park, Bahorok District.The type of data used in this study is primary data obtained through observation and interviews and secondary data through literature and the North Sumatra Central Statistics Agency. Determination of the sample by Purposive Sampling with 100 cattle breeders. Data analysis was carried out by calculating income, financial analysis of Net Present Value (NPV), Net Benefit-Cost (B/C), Payback Period (PP), and economic analysis. The results of this study indicate that the average income of cattle breeders in the Buffer Zone of Gunung Leuser National Park, Bahorok District is IDR 24,551,421 for semi-intensive and IDR 8,235,155 for extensive per year. The income of breeders can cover production costs so that income is positive or profitable. The cattle farming business shows that by using an interest rate of 8%, the NPV is obtained >0 or has a positive value, the Gross B/C value is obtained 1.97 and the Net B/C value is 1.25, meaning BCR>1 means a positive value, the PP value is 3.1 and 4.2 years, and the economic analysis shows that the cattle farming business has an important role in the economy in Bahorok District